The mediating effect of work engagement in the relationship between workplace bullying and turnover intention among employees in public service agencies - Vanishree, Kanaka Sundar (2021)
The main objective of this research was to examine the mediating effect of work engagement in the relationship between workplace bullying and turnover intention among employees in public service agencies. Workplace bullying is associated with negative consequences on the victims such as turnover intention. This is because the victim who is exposed to workplace bullying might decide to quit the job due to physical and emotional damage. Studies have shown that workplace bullying is prevalent in public agencies of Malaysia. Hence, this study focuses on employees from public service agencies since research has found that the rate of bullying is high in public sector. Little is known about the possible mechanism which can mediate this association even though numerous studies have examined the association between workplace bullying and turnover intention. It has been further added that research on the association between bullying-turnover and work engagement is sparse even though the association between workplace bullying and turnover intention is clear from the literature. This study used a cross-sectional survey design and online questionnaires to collect data from 400 participants with ages ranging from 25 to 60. This research used one of the non-probability sampling methods known as purposive sampling to recruit sample size. Linear regression was used as a statistical analysis method to find the effect between the main study variables. Besides, this study also used PROCESS macro developed by Andrew Hayes to study further on the mediation effect. As hypothesized, work engagement partially mediates the relationship between workplace bullying and turnover intention among employees in public service agencies. The findings of this study will be helpful for the managing body of the public sectors who create strategies to discover a better means of managing bullying behaviours within the organisation so that the employees will remain longer in the organisation. The study also suggests that managing body can focus on increasing the employees’ work engagement to retain the employees since highly engaged employees tend to remain longer in an organisation.